2009
DOI: 10.1089/pop.2008.0044
|View full text |Cite
|
Sign up to set email alerts
|

Worksite Health Promotion: The Value of the Tune Up Your Heart Program

Abstract: Successful wellness initiatives at DaimlerChrysler Canada Incorporated (DCCI) led to a unique partnership between key stakeholders that allowed implementation of Tune Up Your Heart, a program aimed at improving workforce cardiovascular disease (CVD) risk. Volunteers were screened and stratified according to their CVD risk. Interventions were tailored to risk level and included goal setting, monitoring progress, and company-wide education programs. Outcome data (CVD risk and components of risk) were collected a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 27 publications
(27 reference statements)
1
8
0
Order By: Relevance
“…2, 3 Because of the adverse impact of physical inactivity and obesity on health care costs, many organizations have initiated ‘wellness' programs, which may include facilities at the work site to encourage exercise. 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18 Although these programs have often resulted in improved fitness for participants, weight loss has been more difficult to achieve. 5, 6, 13, 14, 17 …”
Section: Introductionmentioning
confidence: 99%
“…2, 3 Because of the adverse impact of physical inactivity and obesity on health care costs, many organizations have initiated ‘wellness' programs, which may include facilities at the work site to encourage exercise. 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18 Although these programs have often resulted in improved fitness for participants, weight loss has been more difficult to achieve. 5, 6, 13, 14, 17 …”
Section: Introductionmentioning
confidence: 99%
“…The Canadian Tune Up Your Heart Program, 8 described earlier, proved an effective intervention. A 2001 study of participants in the United Auto Workers-General Motors LifeSteps Health Promotion Program showed that improvements in health risks correlated with an increase in program participation.…”
Section: Discussionmentioning
confidence: 98%
“…A program at Daimler Chrysler in Canada showed improvement in the overall cardiovascular risk profile among participants in their ''Tune Up Your Heart Program.'' 8 Although the majority of the patients in this program were at low cardiovascular risk at the beginning of the program, the additional shift toward lower risk was significant: At baseline, 68.5% of participants were low cardiovascular risk, 21.6% were moderate risk, and 9.9% were high risk. At the end of the study, 71.1% of the intervention group were stratified as low risk, 21.6% were moderate risk, and 7.3% were high risk.…”
Section: Introductionmentioning
confidence: 87%
“…When properly designed, workplace wellness is an effective prevention strategy to improve worker productivity. [53][54][55][56] A number of studies provide evidence of medical and insurance costs for participants in health promotion programs, particularly programs involving exercise. For example, one study reported that participation in a worksite fitness center was associated with 1.3 days fewer short-term disability days per year per employee (P = 0.02).…”
Section: Discussionmentioning
confidence: 99%